Evaluation of small-scale farmland water conservancy construction mode in China - Hambebo, Belachew D.; Li, Hui (Journal of Water and Land Development, 2022)
This study aims to evaluate the construction mode of small-scale farmland water conservancy using secondary data from the China statistical yearbook (2000–2019), which was simply and statistically computed. To put it briefly, the simple linear regression model was used to analyse the number of small-scale reservoirs and irrigated areas relative to their capacities and effectiveness. The results showed that the number of small-scale reservoirs increased by 122.2 units of their capacity and the number of small-scale irrigated areas increased by 6.8 units of their effectiveness. The present study introduces the simple linear regression model and accounts for how the number of the small-scale reservoirs and irrigated areas has increased (the total number of reservoirs was 83,260 in 2000 and 98,822 in 2018) relative to their capacity and effectiveness, respectively. Of course, the capacity of water harvesting and the effectiveness of irrigated areas have shown a linear increase over time. Between 2000 and 2019, the capacity increased from 3842 to 7117 for large-scale reservoirs, from 746 to 126 for medium-scale reservoirs, and from 594 to 710 for small-scale reservoirs and their ranges were 3.2, 380, and 116, respectively. Furthermore, the findings of this evaluation provide insights for making decisions on water conservancy interventions.